Pengembangan Moderasi Mazhab di Kalangan Mahasiswa Perbandingan Mazhab dan Hukum UINAM: Relevansi Pemikiran Islam Moderat - Idrus, Achmad Musyahid; Mustafa, Adriana; Asti, Mulham Jaki (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2022)
This article aims to unravel the development of religious moderation for students, especially students of Comparative Schools and Law of UIN Alauddin Makassar. The approach taken is an approach with issues of moderation. The results showed that the development of moderation in the Comparative Study Program of Schools and Law has gone well and needs to be improved again both in lecture situations and interactions in society. Moderation is a mandatory material for students to understand because moderation is one of the ways to be able to implement religious moderation more broadly. The challenge of Muslims today is with the emergence of sects of sects of sects of fanaticism that led to the birth of the forerunners of acts of radicalism or violence in the name of religion. Debriefing students comparing schools and laws through the development of moderation is a must to counteract understandings that come out of sharia teachings.